THU0389 The Effects of Antihypertensive Drugs on Bone Mineral Density in Ovariectomized Mice. (23rd January 2014) - Kang, K. Y.; Kang, Y.; Hong, Y. S.; Ju, J. H.
Abstract : Background: Antihypertensive drugs impact osteoporosis directly and indirectly by affecting bone metabolism. Because antihypertensive drugs are widely used for the treatment of hypertension, it is important to understand the effects of these drugs on bone density (1 ). Objectives: The effects of several antihypertensive drugs on bone mineral density and micro-architectural changes in ovariectomized (OVX) mice were investigated. Methods: Eight-week-old female C57/BL6 mice were used for this study. Three days after ovariectomy, mice were treated intraperitoneally with nifedipine (15 mg/kg b.w.), telmisartan (5 mg/kg b.w.), enalapril (20 mg/kg b.w.), propranolol (1 mg/kg b.w.) or hydrochlorothiazide (12.5 mg/kg b.w.) for 35 consecutive days. Uterine atrophy confirmed estrogen deficiency. Bone mineral density (BMD) and micro-architectural analyses were performed on tibial proximal ends by micro-computed tomography (micro-CT). Results: When OVX mice with uterine atrophy were compared with mice without atrophy, BMD decreased ( p <0.001). There were significant differences in BMD loss between different antihypertensive drugs ( p =0.005). By post hoc analysis, enalapril and propranolol increased BMD loss in mice with atrophied uteri compared with control mice. By contrast, thiazide increased BMD in mice with uterine atrophy compared with vehicle-treated mice ( p =0.048). Thiazide ( p =0.032) and telmisartan ( p =0.05) reduced bone loss and bone fraction in mice with uterine atrophy compared with the control. BMD also correlated with bone volume and fraction, and trabecular number and thickness by micro-CT analysis. Conclusions: Thiazide affects BMD in OVX mice positively. The reduction in bone loss by thiazide and telmisartan suggest that these drugs may benefit menopausal women with hypertension and osteoporosis. References: Ott SM, LaCroix AZ, Scholes D, Ichikawa LE, Wu K 2008 Effects of three years of low-dose thiazides on mineral metabolism in healthy elderly persons. Osteoporos Int 19 (9): 1315-22. Disclosure of Interest: None Declared